Urban–Rural Differences in the Determinants of Depression Among Mothers of Children Under Five in Indonesia - Wurisastuti, Tri; Martini, Santi; Masitoh, Siti; Irmansyah (Journal of Population and Social Studies [JPSS], 2026)
Mothers of children under five are vulnerable to depression, which may adversely affect child growth and development. This study examined urban–rural differences in the biopsychosocial determinants of maternal depression in Indonesia. Data were obtained from the 2023 Indonesia Health Survey and included 70,851 mothers with children aged 0–59 months. Depressive symptoms were assessed using the Mini International Neuropsychiatric Interview, and determinants were analyzed using multiple logistic regression. In urban areas, maternal depression was associated with younger maternal age (15–19 years; adjusted odds ratio (AOR) = 4.14, 95% CI [2.15, 7.94]), current pregnancy (AOR = 2.30, 95% CI [1.54, 3.43]), and chronic disease (AOR = 2.87, 95% CI [2.08, 3.95]), unintended pregnancy (AOR = 3.50, 95% CI [2.76, 4.44]), divorced status (AOR = 2.61, 95% CI [1.59, 4.27]), unemployment (AOR = 1.80, 95% CI [1.43, 2.28]), and lower educational attainment. In rural areas, depression was associated with chronic disease (AOR = 2.24, 95% CI [1.37, 3.66]), unintended pregnancy (AOR = 2.66, 95% CI [1.79, 3.95]), unemployment (AOR = 1.51, 95% CI [1.15, 1.98]), and divorced status (AOR = 3.45, 95% CI [1.94, 6.14]). These findings demonstrate distinct urban–rural patterns in the determinants of maternal depression, highlighting the importance of context-specific maternal mental health interventions.